INTEGRATING FUNCTIONAL FOODS INTO HOTEL DINING: A MARKET-DRIVEN APPROACH (International Journal of Food and Nutritional Sciences, 2021)
Abstract: Integrating functional foods into hotel dining presents a significant opportunity for enhancing guest experience and promoting health through nutrition. This research explores a market-driven approach to incorporating functional foods—those enriched with bioactive compounds that provide health benefits beyond basic nutrition—into hotel menus. By analyzing current market trends, consumer preferences, and potential health benefits, this study aims to provide a strategic framework for hoteliers to effectively integrate functional foods into their offerings. The research employs a mixed-methods approach, including consumer surveys, industry interviews, and case studies of successful implementations. Key findings indicate that while there is growing consumer interest in functional foods, successful integration requires a balance between culinary innovation and market demand. The study concludes with recommendations for hotels on how to design, market, and implement functional food options in a way that aligns with consumer expectations and enhances the overall dining experience.